Feline Epilepsy: An update - BAKA, RD; POLIZOPOULOU, ZS (Journal of the Hellenic Veterinary Medical Society, 2020)
Epileptic seizures are the most common neurological disorder in the clinical setting. Their etiology is multifactorial and is mainly divided into structural, reactive and idiopathic epilepsy. Structural epilepsy can be caused by vascular events, inflammatory conditions (encephalitis), traumatic injuries, neoplasia, congenital and inherited (degenerative) disorders. Reactive epilepsy is caused by exposure in toxins or metabolic derangements. Although idiopathic epilepsy was thought to be rare in cats, it is now established as a common cause. Epileptic seizures in cats appear with various clinical presentations including generalized, focal with or without secondary generalization epileptic seizures. Diagnostic investigation is crucial in order to establish final diagnosis and to determine the therapeutic plan. Diagnostics include physical and neurological examination with detailed history (drug or toxin exposure), routine hematology (CBC, biochemistry, urinalysis), specific laboratory tests if concurrent or metabolic disease are suspected, advanced diagnostic imaging (CT/MRI) whether intracranial disease is suspected and cerebrospinal fluid (CSF) analysis. Most commonly used antiepileptic drugs (AED) in cats are phenobarbital and levetiracetam. Bromide is contraindicated in cats due to severe respiratory disease caused as an adverse life-threatening reaction. Diazepam is an emergency AED used to eliminate cluster seizures or status epilepticus but it should be avoided as a long-term medication because it has been associated with fatal hepatotoxicity. Gabapentin in another potential antiepileptic drug however its longterm efficacy has to be evaluated. Prognosis depends on the underlying etiology and treatment response. In most cats quality of life is improved and (>50% reduction of epileptic seizures) regardless of etiology. The complete remission of epileptic seizures in cats is rare and most cats should be maintained on anti-epileptic therapy.